1985
DOI: 10.1097/00007890-198510000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Infections in Liver Transplant Recipients

Abstract: Sixty-two adults who underwent orthotopic liver transplantations between February 1981 and June 1983 were followed for a mean of 170 days after the operation. Twenty-six patients developed 30 episodes of significant fungal infection. Candida species and Torulopsis glabrata were responsible for 22 episodes and Aspergillus species for 6. Most fungal infections occurred in the first month after transplantation. In the first 8 weeks after transplantation, death occurred in 69% (18/26) of patients with fungal infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
144
2
8

Year Published

1988
1988
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(164 citation statements)
references
References 18 publications
8
144
2
8
Order By: Relevance
“…In early studies, the incidence of IFI in this setting ranged from 18% to 42%, and the associated mortality rates were 50% to 78%. [1][2][3][4][5][6] Candida species accounted for the majority of infections, and many patients infected with Candida organisms survived. In contrast, infections caused by Aspergillus species were nearly always fatal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In early studies, the incidence of IFI in this setting ranged from 18% to 42%, and the associated mortality rates were 50% to 78%. [1][2][3][4][5][6] Candida species accounted for the majority of infections, and many patients infected with Candida organisms survived. In contrast, infections caused by Aspergillus species were nearly always fatal.…”
mentioning
confidence: 99%
“…In contrast, infections caused by Aspergillus species were nearly always fatal. 2,3,6 We showed that in liver transplant recipients considered high risk for IFI, fluconazole prophylaxis reduced the incidence of invasive candidiasis 7 but was complicated by the emergence of fluconazole-resistant fungi and failed to prevent invasive aspergillosis. 8 A recent randomized, placebo-controlled trial of liver transplant recipients showed that prophylaxis with fluconazole was associated with a decrease in fungal colonization and fewer deaths related to IFI, but did not improve overall survival.…”
mentioning
confidence: 99%
“…Cases of invasive aspergillosis have been reported after transplantation of the liver [2][3][4][5][6], kidney [1,[7][8][9][10][11], and heart [12][13][14][15]. Aspergillosis was diagnosed in 9 % of adult liver transplant recipients who received immunosuppressive therapy consisting of administration of azathioprine, prednisone, and antilymphocyte globulin [2].…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillosis was diagnosed in 9 % of adult liver transplant recipients who received immunosuppressive therapy consisting of administration of azathioprine, prednisone, and antilymphocyte globulin [2]. Similarly, 6 % of adult liver transplant recipients treated with cyclosporine and prednisone developed aspergillosis [3,4] . All patients with aspergillosis from those three series of liver transplantations [2][3][4] [1,[7][8][9][10][11] has survived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation